The Effectiveness of Sea Lettuce (Ulva Lactuca) Water Extract from Aceh Waters as an Anti-Obesity - Rinawati Rinawati; Sri Wahyuni Muhsin (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2022)
Obesity is a condition of weight excess above average weight. Obesity can happen due to calories continuing into the body without being offset by physical activity. This study aims to determine the effectiveness of the water extract of Ulva Lactuca against weight loss in obese mice. type of research used is laboratory experiments using the design posttest only control group design research. we grouped into 7 groups, namely: normal Control, Positive Control, Treatment Control, P1= the group of obese mice + extract 300 mg/kg, P2= the group of obese mice + extract 400 mg/kg, P3= the group of obese mice + extract 500 mg/kg P4=the group of obese mice + orlistat.The Aqueous Extract of Ulva Lactuca has not been able to lose obese mice for 28 days of treatment. Normal mice in treatment of the Extract did not show changes in body weight